Uncertainty about the fundamentals and the occurrence of sudden stops of capital flows: Theory and Empirics - Fritzi Koehler-Geib (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
We analyse the effect of the uncertainty about the fundamentals on the probability of sudden stops of capital flows from a theoretical and empirical perspective. Our model predicts that the probability of crises increases with the uncertainty, ie. the dispersion of private signals about the true value of the fundamentals. Using two datasets of Consensus and WES forecasts for 31 developed and developing countries for the time period from January 1990 until December 2001 we verify the theoretical prediction. We apply probit estimation controlling for time and country effects. Additionally, we show that the result is robust for numerous specifications.
Keywords: C72; D82; D84; F21; F32; F34; F41; 330; Capital Flows; Government debt; Sudden Stops; Global Games; Coordination Failure